2020
DOI: 10.1016/j.cub.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Organization in Early Land Plants Reveals an Ancestral Association between H3K27me3, Transposons, and Constitutive Heterochromatin

Abstract: Highlights d A database combining genomic information and chromatin profiles for Marchantia d Correlations between chromatin marks and transcription are conserved in land plants d A significant portion of constitutive heterochromatin is marked by H3K27me3 d Insights into the evolution of TAD organization in plants

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 113 publications
6
179
0
1
Order By: Relevance
“…An intriguing puzzle to solve in the near future is how H3K27me3 can confer instability on a molecular level, and why this mechanism evolved over evolutionary timescales. While functional studies on the molecular mechanism are still lacking, a recent study on early land plants suggested that H3K27me3 together with H3K9me3 might represent an ancient form of genome defense mechanism against transposons [156]. Regions enriched with H3K9me2/3 and DNA cytosine methylation are usually AT-and repeat-rich, and movement of H3K27me3 to these regions in absence of H3K9me3 hints to a compensatory genome defense mechanism that was previously proposed to act in animals [152].…”
Section: Evolution Of H3k27me3-dependent Transcriptional Silencing Frmentioning
confidence: 99%
“…An intriguing puzzle to solve in the near future is how H3K27me3 can confer instability on a molecular level, and why this mechanism evolved over evolutionary timescales. While functional studies on the molecular mechanism are still lacking, a recent study on early land plants suggested that H3K27me3 together with H3K9me3 might represent an ancient form of genome defense mechanism against transposons [156]. Regions enriched with H3K9me2/3 and DNA cytosine methylation are usually AT-and repeat-rich, and movement of H3K27me3 to these regions in absence of H3K9me3 hints to a compensatory genome defense mechanism that was previously proposed to act in animals [152].…”
Section: Evolution Of H3k27me3-dependent Transcriptional Silencing Frmentioning
confidence: 99%
“…TEs are maintained in silent form either by changes in the chromatin structure or directly by cytosine methylation of their sequences in CG, CHG and CHH contexts [52]. DNA methylation in a CHH context is the signature of RNA-directed DNA methylation, RdDM [53,54].…”
Section: Consequences Of Te Location and Sirna Production Nearby In Gmentioning
confidence: 99%
“…We followed the nomenclature of genes, proteins, and mutants of Marchantia reported in Bowman et al 66 . Gene IDs were taken from MarpolBase (http://marchantia.info/), genome version 3.1 and version 5.1 27,67 .…”
mentioning
confidence: 99%